Experiments in Buddhist-Christian encounter: from Buddha-nature to the divine nature - Feldmeier, Peter (Orbis Books, 2018)
The importance of the religious other -- The Buddha and his teaching -- The path of purification and the dark night: Buddhaghosa and John of the Cross -- Nagarjuna and the Christian via negativa -- Emptiness, Buddha-nature, Bodhisattvas, and Meister Eckhart -- The way of the Bodhisattva and the spiritual exercises -- Zen mind/Christian mind -- Zen oxherding pictures and the stages of faith -- The heart of Buddhist experience, pure land, and Christian theology -- A Christian commentary on the Heart Sutra